2011
DOI: 10.1089/tmj.2011.0032
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Weight Reported in a Web-Based Obesity Treatment Program

Abstract: Objective: The overall goal of the study was to understand the accuracy of self-reported weight over a 6-month Web-based obesity program. Materials and Methods: As part of a larger study, subjects (n = 323; 93% female; 28% African American) were randomized to a 6-month Internet-based behavioral weight loss program with weekly group meetings delivered either: (1) entirely by online synchronous chats or (2) by a combination of online chats plus monthly in-person group sessions. Observed weights were obtained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 8 publications
9
29
0
Order By: Relevance
“…Specifically, participants’ self-report resulted in a modest, yet significant underestimation of weight consistent with previous findings from cross-sectional studies and weight-loss trials [4,5,9,10]. The magnitude of underestimation doubled between Months 6 and 24.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, participants’ self-report resulted in a modest, yet significant underestimation of weight consistent with previous findings from cross-sectional studies and weight-loss trials [4,5,9,10]. The magnitude of underestimation doubled between Months 6 and 24.…”
Section: Discussionsupporting
confidence: 86%
“…However, recent analyses of reported vs observed weights in an online weight loss study found that self-reported and measured weights were significantly correlated. 39 Therefore, the authors feel confident that the weight data are valid. The study was also not a randomized-controlled trial, and therefore causal conclusions cannot be made.…”
Section: Discussionmentioning
confidence: 94%
“…The study is also limited by reliance on self-reported weights. However, weight reported by members of another online weight loss program was highly correlated with and similar to objective weights [35]. The lack of date stamps on most website usage variables (except log-ins and weight entries) limited the depth of analysis on the intensity and patterns of website usage.…”
Section: Discussionmentioning
confidence: 99%